Tuscan black kale sprout extract bioactivated with myrosinase: a novel natural product for neuroprotection by inflammatory and oxidative response during cerebral ischemia/reperfusion injury in rat - Giacoppo, Sabrina (BMC Complement Altern Med, 2015)
BACKGROUND: Cerebral ischemia and reperfusion (CIR) is a pathological condition characterized by a first blood supply restriction to brain followed by the consequent restoration of blood flow and simultaneous reoxygenation. The aim of this study was to evaluate the neuroprotective effects of Tuscan black kale sprout extract (TBK-SE) bioactivated with myrosinase enzyme, assessing its capability to preserve blood–brain barrier (BBB), in a rat model of CIR. METHODS: CIR was induced in rats according to a classic model of carotid artery occlusion for a time period of 1 h and the reperfusion time was prolonged for seven days. RESULTS: By immunohistochemical evaluation and western blot analysis of brain and cerebellum tissues, our data have clearly shown that administration of bioactive TBK-SE is able to restore alterations of tight junction components (claudin-5 immunolocalization). Also, bioactive TBK-SE reduces some inflammatory key-markers (p-selectin, GFAP, Iba-1, ERK1/2 and TNF-α), as well as the triggering of neuronal apoptotic death pathway (data about Bax/Bcl-2 balance, p53 and cleaved-caspase 3) and the generation of radicalic species by oxidative stress (results focused on iNOS, nitrotyrosine and Nrf2). CONCLUSION: Taken together, our findings lead to believe that bioactive TBK-SE exerts pharmacological properties in protecting BBB integrity through a mechanism of action that involves a modulation of inflammatory and oxidative pathway as well into control of neuronal death.